Lifetime ATS use and increased HIV risk among not-in-treatment opiate injectors in Malaysia. - Chawarski, Marek C; Vicknasingam, Balasingam; Mazlan, Mahmud; Schottenfeld, Richard S (Drug and alcohol dependence, 2012)
Malaysia has been experiencing significant drug abuse problems since the 1970s, and drug abuse is the major driver of HIV transmission in Malaysia. We investigated risk factors for HIV associated with use of amphetamine type stimulants (ATS) among not-in-treatment opiate injectors in Malaysia.
Keywords: Adult; Amphetamines; Central Nervous System Stimulants; Female; HIV Infections; HIV Seropositivity; Humans; Malaysia; Male; Middle Aged; Needle Sharing; Opioid-Related Disorders; Risk; Risk Factors; Risk-Taking; Street Drugs; Substance Abuse, Intravenous